Designing and codifying a test to measure the speed and ability to pass and receive the ball in a collective fast attack for Iraqi handball club players - Fathi , Moushriq; Hadi , Zahraa; Hussein , Yasir (Journal of Physical Education, 2024)
The recent amendments to the rules of the law of the game have contributed effectively to raise  the pace of competition by increasing the speed of the game’s rhythm to revolutionize this field. Therefore, most international and local teams have begun to change training methods to reflect this on the style of playing and the concentration of those teams has shifted to the fast attack that is characterized by ease and scoring goals quickly to achieve victory so that the dominant character of the game becomes fast rhythm playing. All handball players should have the capabilities that qualify them to meet the requirements of the game which helps to determine the level of ball passing skills among handball players in a collective fast attack to perform shots on goal skillfully with high accuracy. Hence, it requires the availability of means or tests to measure the capabilities of the players, and here lies the importance of this study, but if these tests are found, they are rare or not sufficient for the purpose, and here lies the problem of the study. Therefore, the researchers agree to delve into this matter to develop appropriate solutions by designing a modern measurement method or a special test so that researchers, coaches and handball players alike can benefit from the test as a humble service from the researchers of this paper towards the game. The study is conducted on some club players participating in the Iraqi Handball League. The main goal of this study is to design and codify a special test to measure the ability of the players to perform a fast collective attack. Additionally, as for the areas of study, the researchers rely on some club players participating in the Iraqi Handball League. The study is performed on 10th Mar, 2021 until 20th Jul, 2022. The procedures of the test are conducted in the stadiums of the clubs participating in the Iraqi Handball League. The study employs a general qualitative approach. The researchers also employ quantitative methods to highlight the percentages, the arithmetic mean, the standard deviation, the simple correlation coefficient, the T test, the standard score, and the modified standard score. The researchers conclude from the results they achieved that this test, which is designed and codified, is characterized by high accuracy and adequacy, and can be used to measure the speed and ability to pass and receive the ball in the collective fast attack of handball players which is the reason for designing such test. The researchers support employing such tests to measure the speed and effectiveness of handball players’ performance of the fast attack process in order to properly evaluate their performance before and during the championships. The researchers also urge to devise other tests on different samples.